2009
DOI: 10.2118/114173-pa
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating Unconventional Reservoirs: Maximizing Network Growth While Optimizing Fracture Conductivity

Abstract: Unconventional reservoirs such as gas shales and tight gas sands require technology-based solutions for optimum development. The successful exploitation of these reservoirs has relied on some combination of horizontal drilling, multi-stage completions, innovative fracturing and fracture mapping to engineer economic completions. However, the requirements for economic production all hinge on the matrix permeability of these reservoirs, supplemented by the conductivity that can be generated in hydraulic fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(85 citation statements)
references
References 41 publications
0
85
0
Order By: Relevance
“…This schedule was designed for a vertical well; horizontal wells typically use between four and eight times more water. Hydraulic fracture stimulation in gas shales typically increases fracture conductivity to between 0.5 and 10 md-ft, which represents an overall increase in formation permeability between 1 and 7 orders of magnitude, depending on the width of the fractures; larger permeability values lead to greater gas recovery (Warpinski et al, 2008).…”
Section: Stimulationmentioning
confidence: 99%
“…This schedule was designed for a vertical well; horizontal wells typically use between four and eight times more water. Hydraulic fracture stimulation in gas shales typically increases fracture conductivity to between 0.5 and 10 md-ft, which represents an overall increase in formation permeability between 1 and 7 orders of magnitude, depending on the width of the fractures; larger permeability values lead to greater gas recovery (Warpinski et al, 2008).…”
Section: Stimulationmentioning
confidence: 99%
“…Proppants such as sand and ceramic with small size are injected with the fluid into the fractures, which can hold fractures open to provide a conductive path for fluid flow from reservoir to wellbore. Multiple long hydraulic fractures with uniform proppant distribution and sufficient fracture conductivity play an important role in achieving effective well stimulation and economic production of shale reservoirs [1][2][3][4][5][6][7]. Cipolla et al [8] studied the effect of proppant distribution in the fracture network on well performance and showed that proppant distribution significantly affects the fracture network conductivity and treatment design.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic fracturing has been widely implemented for the exploitation of oil, gas, and geothermal resources (Hubbert and Willis 1957;Warpinski et al 2009;Beckwith 2010). The current numerical simulations mainly focused on the propagation of single fractures (Paris and Erdogan 1963;Hoek and Bieniawski 1965;Germanovich et al 1994;Olson 2004;Yang et al 2013) and several fractures (Bobet and Einstein 1998;Sagong and Bobet 2002;Yang et al 2012;Li J et al 2013), yet investigating the hydraulic fracturing behavior of complex fracture networks is still a great challenge because of the complex rock-fluid mechanisms involved and the time-consuming computation (Zhao et al 2014b).…”
Section: Concluding Remarks and Future Workmentioning
confidence: 99%